2014
DOI: 10.4103/1008-682x.129940
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction models for biochemical recurrence after radical prostatectomy using prostate-specific antigen and Gleason score

Abstract: Many computer models for predicting the risk of prostate cancer have been developed including for prediction of biochemical recurrence (BCR). However, models for individual BCR free probability at individual time-points after a BCR free period are rare. Follow-up data from 1656 patients who underwent laparoscopic radical prostatectomy (LRP) were used to develop an artificial neural network (ANN) to predict BCR and to compare it with a logistic regression (LR) model using clinical and pathologic parameters, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…In our final cohort with available 437 patients (95% of 460 operated men) and complete follow up after RP from 2001 to 2014 we first represent PHI as a prognostic biomarker based on long term data. While most patients develop a BCR within the first two years, some have a recurrence of up to five years after RP [ 25 ]. We believe that a sufficient prediction regarding a possible BCR can only be made after a median follow up of at least 5 years because the number of BCR cases in the years 5 to 10 after RP are relatively low and decreasing continuously [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our final cohort with available 437 patients (95% of 460 operated men) and complete follow up after RP from 2001 to 2014 we first represent PHI as a prognostic biomarker based on long term data. While most patients develop a BCR within the first two years, some have a recurrence of up to five years after RP [ 25 ]. We believe that a sufficient prediction regarding a possible BCR can only be made after a median follow up of at least 5 years because the number of BCR cases in the years 5 to 10 after RP are relatively low and decreasing continuously [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most patients develop a BCR within the first two years, some have a recurrence of up to five years after RP [ 25 ]. We believe that a sufficient prediction regarding a possible BCR can only be made after a median follow up of at least 5 years because the number of BCR cases in the years 5 to 10 after RP are relatively low and decreasing continuously [ 25 ]. The data of this study supports this since 83.2% are recurrence free after 5 years, 78.6% after 8 years and 77.2% are recurrence free after 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to evaluate the dependence of the PR on PSA level and PSA kinetics, and to identify the lowest PSA threshold that detects local, regional or systemic relapse of PC, using 68Ga-PSMA-11 PET/CT. We retrospectively analyzed PSA levels after primary therapy for PC as well as PSA levels at resubmission for BCR in a large cohort of patients taking the Gleason Score (GS is the world’s established PC grading system and used for the histopathological assessment of the glandular morphology of the prostate; since PC is often inconsistent and may have significantly different areas, two areas are generally assessed for GS; biologically significantly more aggressive tumors must be assumed in findings with GS 4+3=7b, 4+4=8, 4+5=9 and 5+4=9 [5, 11, 25]), determined after resection, and anti-androgen therapy ( AT) into account.…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with other studies. 15 16 Preoperative PSA level as a factor predicting BCR was validated in most of the available studies. In this study, we also confirmed that PSA level at diagnosis, as well as short-term PSA after RP, was a significant predictor of BCR and BCR-free survival after adjusting other potential factors.…”
Section: Discussionmentioning
confidence: 99%